Enrichment of Circulating Tumor Cells from Whole Blood Using a Microfluidic Device for Sequential Physical and Magnetophoretic Separations - Jusin Lee; Onejae Sul; Seung-Beck Lee (Micromachines, 2020)
Based on their high clinical potential, the isolation and enrichment of rare circulating tumor cells (CTCs) from peripheral blood cells has been widely investigated. There have been technical challenges with CTC separation methods using solely cancer-specific surface molecules or just using physical properties of CTCs, as they may suffer from heterogeneity or lack of specificity from overlapping physical characteristics with leukocytes. Here, we integrated an immunomagnetic-based negative enrichment method that utilizes magnetic beads attached to leukocyte-specific surface antigens, with a physical separation method that utilizes the distinct size and deformability of CTCs. By manipulating the pressure distribution throughout the device and balancing the drag and magnetic forces acting on the magnetically labeled white blood cells (WBCs), the sequential physical and magnetophoretic separations were optimized to isolate intact cancer cells, regardless of heterogeneity from whole blood. Using a breast cancer cell line in whole blood, we achieved 100% separation efficiency for cancer cells and an average of 97.2% for WBCs, which resulted in a 93.3% average separation purity. The experimental results demonstrated that our microfluidic device can be a promising candidate for liquid biopsy and can be a vital tool for aiding future cancer research.